1980
DOI: 10.1111/j.1469-8137.1980.tb04775.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Nutrition of Pasture Plants Ii. Effect of Sodium Chloride on Growth, Chemical Composition and the Reduction of Nitrate Nitrogen

Abstract: The effect of increasing concentrations of sodium chloride in the root zone on growth, chemical composition and nitrate reductase activity of perennial ryegrass and timothy was investigated in a glasshouse pot experiment. For ryegrass, a natrophile, sodium chloride had little effect on growth, whereas for timothy, a natrophobe, growth was severely depressed by comparatively low concentrations of salt. The result also indicate that translocation of sodium into the leaves of timothy took place readily only after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…It has indeed been observed that the Na concentration of timothy increases when plants age (Jarvis 1982). The same phenomenon, in a weaker form, has been observed with perennial ryegrass, meadow fescue and cocksfoot (Rinne et al 1974, Smith et al 1980.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…It has indeed been observed that the Na concentration of timothy increases when plants age (Jarvis 1982). The same phenomenon, in a weaker form, has been observed with perennial ryegrass, meadow fescue and cocksfoot (Rinne et al 1974, Smith et al 1980.…”
Section: Discussionsupporting
confidence: 63%
“…Introduction mals, and forage should contain Na 1.8-2g kg 1 of dry matter to supply milking cows with sufficient Na (NJF 1975, Smith and Middleton 1978, Horn 1988. Thus, there is a big difference between the requirement of cattle and the supply of Na from farm-produced fodder in Finland, and it has to be compensated with mineral supplements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature was not allowed to rise above 5 °C during the extraction and determination of chlorophyll. Harvested tissue not used for chlorophyll estimations was dried at 90 ''C, weighed and analysed for major and minor elennents by the procedures summarized by Smith, Middleton and Edmonds (1980). Iron concentrations in solution were: (Fej) those recommended in the original publications (see Table 1); (Fe^) modified so that maize was grown with 10 /tg iron ml"* and ryegrass and white clover with 3/ig iron Electrical conductivity and pH were measured on the solution surrounding the roots just before the final harvest of the plants.…”
Section: Measurementmentioning
confidence: 99%
“…Elles concernent généralement la première (Strogonov, 1964 ;Helal et Mengel, 1979 ;Smith et al, 1980 ;Lucque et Bingham, 1981 ;Aslam et al, 1984). À faible dose, les sels ont peu d'effet sur l'alimentation nitrique; mais à forte dose, ils inhibent l'absorption et le transport de NO -3 , la réduction étant la fonction la moins touchée (Lucque et Bingham, 1981;Aslam et al, 1984).…”
unclassified